Inhibitory effects of caffeic acid ester analogues on free radicals and human liver microsome CYP1A2 activities - Jaikang C. (2014)
Ethyl caffeate (EC), octyl caffeate(OC), benzyl caffeate(BC) and phenethyl caffeate(PC) were synthesized and evaluated for scavenging of superoxide anion, nitric oxide radical and 1,1-diphenyl-1-picrylhydrazyl radical(DPPH). Antioxidant activity was investigated with reducing power method. Pooled human liver microsome was used for investigating the effects on cytochrome P450 1A2 (CYP1A2) catalytic activities by using phenacetin as a substrate. Dixon and Cornish-Bowden plots were used for enzyme kinetic analysis. The EC, OC, BC and PC potentially inhibited superoxide anion, nitric oxide and DPPH radicals. IC50 values of superoxide anion scavenging of EC, OC, BC and PC were 16.42, 79.83, 123.69 and 123.69 μg/ml, respectively. EC was more potent than OC and BC in terms of nitric oxide radical scavenger: IC50 values of EC, OC and BC were 24.16, 37.34 and 52.64 μg/ml, respectively. In addition, the IC50 values of EC, OC, BC and PC on DPPH radical scavenging were 70.00, 184.56, 285.34 and 866.54 μg/ml, respectively. The IC50 values of EC, OC, BC and PC on phenacetin O-deethylation were 124.98, 111.86, 156.68 and 31.05 μg/ml, respectively. Enzyme kinetics showed that the type of inhibition mechanism was mixed-type. The result of this study shows that caffeic acid ester analogues potentially scavenge free radicals and inhibit catalytic activity of CYP1A2. This may lead to important implications in the prevention of CYP1A2-mediated chemical carcinogenesis. © 2011 Bentham Science Publishers Ltd.